Civil Discourse and Social Change: A University-wide, Faculty-led Social Justice Initiative within the Neoliberal University - Daniel Olmos; Stevie Ruiz; Aimee Carrillo Rowe; Martha Escobar (Ali Khorsandi Taskoh, 2023)
As U.S. colleges and universities experience increasing diversity and contend with various socio-economic inequities, the university is becoming a site of struggle for reclaiming higher education as a democratic public sphere for social justice. We reflect on the institutional articulation of social justice in higher education by examining a multi-year effort by faculty in various departments to promote social justice education and activism across a large regional public Hispanic Serving Institution (HSI) university in Southern California. While addressing the tensions between social justice and the neoliberal university, we explore the organizational and pedagogical dimensions of the faculty-led social justice initiative and examine its curricular and cocurricular educational impacts on critical thinking, democratic engagement, and anti-oppressive transformational consciousness among traditionally underserved university students of color. We conclude by discussing implications for social justice-oriented faculty leaders seeking to promote social justice within the neoliberal university which is increasingly under assault by authoritarian forces opposed to democratically engaged and anti-oppressive education. We hope that our social justice project provides lessons on how a coalition of interdisciplinary faculty can effectively push universities to meaningfully embrace social justice education and activism.